Judicial sentencing of minor and juvenile offenders. Remarks in the context of the Polish Criminal Code - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article addresses selected issues related to the status of the minor and the juvenile from the perspective of criminal liability. While analyzing the issues indicated in the title references have been made not only to Article 10 § 2 and 3 of the Criminal Code, but also to Article 54 of the Criminal Code, which contains two specific directives of the judicial imposition of asentence on juvenile offenders.
Keywords: skazanie sądowe; resocjalizacja sprawcy; skazywanie małoletnich lub nieletnich